Novel CLCNKB Mutation in Two Siblings With Classic Bartter Syndrome - Navid Roodaki; Leigh Michelle Salinas; Ebner Bon G. Maceda; Jorelyn Frias (Case Reports in Genetics)
Conclusions: Bartter syndrome Type III is a genetic disorder that must be identified clinically without delay, as it typically manifests as acute dehydration due to polyuria and vomiting. Hydrocephalus, although cannot be concluded to be a complication of Bartter syndrome, can be associated due to several electrolyte imbalances involved in this condition. Genetic testing is essential for identifying unidentified pathogenic variants that will aid future patients diagnosed with this condition. Genetic counseling is of the utmost importance for these families affected by the condition in question.